Carbon Benefits from Growing Trees of Medicinal Importance in Punjab - Chauhan, Suresh; Gera, Mohit (Indian Forester, 2010)
Forestry CDM projects involving plantation of native species offer opportunities for CO2 mitigation by removal of accumulated CO2 in atmosphere and sequester it in vegetation, soil and wood products. Besides being grown for longer periods, tree species of medicinal importance are associated with recurring benefits to the growers, on account of fruits, seeds and other products. The present study on plantation of tree species of medicinal importance such as Amla, Arjun, Bael, Bahera, Harar, Jamun, Neem and Reetha on forest as well as the private lands have shown that there is significantly large sequestration potential in the range of 3.56 to 16.77 tons of CO2 per ha per year with corresponding carbon benefits of Rs. 819/- to Rs. 3,858/- and Rs. 1,638/- to Rs. 7,716/- under carbon prices of $5 and $10 per ton of C02 respectively, on per ha per annum for a project period of 30 years. The study has further shown that the increase in returns on account of carbon revenue is likely to motivate the smallfarmers to optforplantationof these speciesoncommunitylandsandfarm bunds.